HUBUNGAN BIG FIVE PERSONALITY DAN DUKUNGAN SOSIAL SUAMI DENGAN BODY IMAGE PADA PEREMPUAN DALAM PERIODE POSTPARTUM - Christina Fieliani Octavia; Hartanti Hartanti; Vivi Setiono (CALYPTRA, 2018)
Abstract - For many women, body image has been a particular concern throughout life, no exception after childbirth (postpartum). It was inevitable that the body undergoes drastic changed during postpartum period. The purpose of this study was to know the relationship between big five personality and husband’s social support with body image of women in the postpartum period. The participant of study were 60 women gave birth first child, in the postpartum period (1 week - 6 months) and live in Surabaya. The sample was conducted using incidental sampling technique. The data collection use instrument questionnaire. Data analysis techniques to test major hypotheses is multiple regression analysiswhile to test minor hypotheses using partial correlation. Multiple regression analysis showed that there was the relationship between openness to experience, conscientiousness, extraversion, agreeablenes, neuroticism and husband’s support social with body image of women in the period postpartum (R= 0,765). In this study, husband’s social support was predictor for body image of women in the period postpartum (R2 = 0,503). Partial correlation indicated conscientiousness (rparsial= -0,278) and neuroticism (rparsial= -0,326) had a negative correlation with body image. Partial correlation also found that husband’s social support had a positive correlation with body image (rparsial = 0,557).